KETIDAKEFEKTIFAN KALIMAT PADA CAPTION WHATSAPP MAHASISWA FAKULTAS BAHASA DAN SENI UNIVERSITAS INDRAPRASTA PGRI - Siti Mutoharoh; Widi Jihan Nurtari; Irwan Siagian (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2022)
The birth of technology often makes changes to the pattern of people’s lives. It is undeniable that the development of the media also plays an active role in changing one’s lifestyle, both electronic, print and online media. Students of the Faculty of Languages and Arts often share photos of their activities, holidays, or situation at that time. However, the author sees a lot of caption sentences that pay attention to effective sentences. This study aims to find out the general description of the ineffectiveness of sentences in the WhatsApp captions of students of the Faculty of Language and Arts, Indraprasta university, PGRI and to find out what factors are ineffective sentences in the WhatsApp captions of students of Faculty of Language and Arts, Indraprasta University, PGRI. The research focuses on the factors of the ineffectiveness of sentences contained in WhatsApp captions written by students of the Faculty of Language and Arts, Indraprasta University PGRI. The research method used is qualitative research with descriptive analysis techniques. The data was taken for seven days, from September 29 to October 5, 2021. The results showed the data: 19 foreign language influences, 1 pleonasm, 12 ambiguity, 1 reasoning error, 5 ambiguity of the core elements of the sentence, 9 regional language influences, 2 waste of word preposition, 1 inaccuracy of word meaning, and 5 ambiguity of word meaning.